Genomic Approach to Understanding Epidemic Potentials and Tissue Tropism of Enterovirus A71 (EV-A 71) Strains - Mohd Apandi, Yusof (Universiti Malaysia Sarawak (UNIMAS), 2016)
Since its first isolation in 1969, human enterovirus A71 (EV-A71) has been associated with large hand, foot and mouth disease (HFMD) outbreaks in several different countries throughout the world. Although other enteroviruses such as CV-A16, are also associated with large HFMD outbreaks and are generally associated with mild clinical presentations, EV-A71 infections can include neurological complications such as meningitis, acute flaccid paralysis, pulmonary oedema that sometimes have fatal outcomes. There have been concerns as to why some EV-A71 strains were associated with uncomplicated HFMD while others were associated with more severe clinical presentations that sometimes resulted in death. To understand this, full genomes sequences of EV-A71 viruses from all subgenogroups, different geographical areas and isolated from either uncomplicated HFMD, severe and fatal cases were characterized. Sequences comparison of 15 isolates of EV-A71 from this study and other sequences retrieved from the GenBank were done. Phylogenetic analysis was separately done for all individual gene regions, the three P1, P2 and P3 regions and the complete genome sequence. Generally, all analysed regions reflected the three (A, B and C) genogroup clustering that had been previously proposed for EV-A71. No interspecific recombination was observed. The trees of VP4 showed concordant phylogenetic profiles with VP1 and may be useful for quick molecular typing of EV-A71 isolates owing to the smaller genome size of the VP4. Comparing the amino acid sequences for all genes, in the P1 region, VP4 showed 100% conserved amino acids sequences across all subgenogroups. In VP2, 4 amino acid substitutions differentiated between genogroup B from C isolates but were not associated uniquely with any particular clinical presentation (mild, severe and fatal) which suggests that they may not be important in virus virulence. In VP3, substitutions amino acid at 413 and 414 with leucine and glutamic acid were associated with isolates iii from severe and fatal cases but not with isolates from mild/uncomplicated case. The strain TW 2272/98 (isolated from a fatal case) from subgenogroup C2, with variation at several amino acid positions, 708 (S for T), 710 (Q for E), 749 (N for T) and consecutive substitutions from 826 to 830 (ECQTP for AWIPR) and 832-833 (IT for MR) could play a role in virulence and clinical presentation of the diseases. In the P2 region, substitutions of asparagine, serine and alanine at amino acid positions 919, 969 and 986 respectively in the 2A gene and substitutions at positions 1059 and 1097 were observed randomly across isolates from all three genogroups. The 2C gene had the most amino acids differences with 17 in genogroup B and 11 between the genogroups B and C. All these substitutions could not be attributed to differences in strains virulence as isolates from uncomplicated HFMD and fatal cases did not show obvious differences. In the P3 region, the 3A gene had different amino acids in the subgenogroups but not between the genogroups A, B and C. In subgenogroup B, isolates from Singapore and Malaysia were different at positions 1503, 1506, whereas in subgenogroup C, the differences were noted at positions 1484, 1486, 1503, and 1505. The 3B, 3C and 3D genes had amino acids with 86% similarity but no clear association with any particular clinical presentation. These results suggest that virulence of EV-A71 strains may be associated with more than one single amino acid substitution sites and also with differences in the 5’UTR region that play a role in the expression of the viral genome.